Notes about jewish studies in Chile - Tapia Adler, Ana María (Cuadernos Judaicos, 2017)
This article aims to provide a panoramic view of how the state of Jewish studies in Chile is presented, both in the academic field and outside of it, and the areas in which research and seminary work have been carried out in Chilean universities.